The functions of Motor Play and its evolutionary implications in the development of the child - Antonio Ascione (Formazione & Insegnamento, 2022)
With this contribution we want to further elevate the value of the educational contribution that the observation of the game before, and the game itself then, can give to the work of the teacher. The aim is to ask ourselves how the game, as a daily and fundamental element for a harmonious psychophysical growth of the child, can become a fundamental element also for adults and in particular to identify, decrease and counteract increasingly frequent aggressive phenomena in our classes/ sections. Physical activity (PA) and fundamental motor skills are important components of present and future health trajectories in young children. This study examined the effects of a 24-week mobility intervention on the motor competence of kindergarten children. Initial tests were on guided play (research group A) and free play (control group B). 20 preschool children were assessed for motor skills before and after surgery using the tests of long jump from standstill and fast run over a distance of 10 meters. The tests were administered to both groups and immediately before the start of the research, as well as at the end the same tests were administered for the evaluation of the results. All children significantly improved their motor skills from baseline to final assessment. Both Group A children and Group B children have shown slight rates of change, proving that the game is independent of adult control. It stimulates memory, motor language, attention, promotes the development of perceptive patterns and socio-emotional-affective abilities. On the contrary, a poor playful activity can lead to deficiencies in the child’s personal maturity and maturity.